How Green Accounting, Company Size and Company Performance on the Indonesian Sharia Stock Index ? - Indah Oktari Wijayanti; Danang Adi Putra; Febi AJi Riansyah (CV. Ulil Albab Corp, 2024)
This study aims to determine the application of green accounting, company size and company performance with the Indonesian Sharia Stock Index (ISSI). This research uses quantitative research. The population in this study are mining companies listed on the Indonesian Sharia Stock Index (ISSI) for 2021-2023. The sampling technique used in this study used purposive sampling. The number of companies sampled in this study were 807 companies. The type of data used is secondary data, namely in the form of financial reports and annual reports obtained through the official website of the Indonesia Stock Exchange and the official websites of related companies. The dependent variable used in this study is Company Performance. Meanwhile, the independent variables use green accounting and company size. The data analysis method used is panel data regression analysis with the help of the SPSS application program. The results of this study indicate that green accounting and company size have a positive and significant effect on company performance